Alcáçova do Castelo de Mértola : necrópole medieval e moderna - Palma, Maria de Fátima (2015)
Mértola’s Archaeological Site began its work in the Alcáçova of the Castle of Mértola. Since 1978 we uncovered a dense necropolis from the Late Middle Ages/ Early Modern Period, an intricate Islamic neighbourhood and an impressive paleo-christian religious complex that integrates a crypto-porticus, a 6th century baptistery and an interesting collection of mosaics with a strong Byzantine influence, which have been largely studied and divulged. After the Christian conquest, in 1238, this entire area, formerly occupied by the Islamic neighbourhood, was converted by the victors into a graveyard, from which already more than 700 graves were exhumed. In this article we present one of the less known phases of this important site, the Medieval / Modern necropolis, excavated during the last 35 years of research. The more than 700 graves excavated until now brought to light several Archaeological and Anthropological data, which combined allow a better understanding of this necropolis, of the population that inhabited Mértola, and of the innumerable pathologies that were identified. The study of the graves and human remains allows for the characterisation of ancient societies, particularly of their way of life, religious beliefs, funerary rituals, and in some cases of the activities to which the populations dedicated themselves. This is a work in progress, since the excavations in this site are still underway and each year new subjects are exhumed, allowing further study and also the analysis of older data. In spite of the large quantity of excavated graves, a more systematic Anthropological study only began to be realised a few years ago, now showing its first results.